Who speaks for Islam? : what a billion Muslims really think - Esposito, John L. (Gallup Press, 2007)
Draws on in-depth research to offer insights into what Muslims actually believe about key global issues such as democracy, radicalism, and women's rights, in an account that seeks to differentiate extremists from everyday Muslims.